PENERAPAN METODE PERMAINAN KARTU BERPASANGAN UNTUK MENINGKATKAN HASIL BELAJAR SISWA MATA PELAJARAN MATEMATIKA MATERI PECAHAN DI KELAS III SDN 2 BUGEMAN TAHUN PELAJARAN 2013/2014 - Hasiyati Ningsih; Mufarrahatus Syarifah (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Abdurachman Saleh Situbondo, 2015)
This research is a Classroom Action Research which aims to improve students' learning outcomes through the method application of paired card game for students for grade 3 in mathematics subject academic year 2012/2014. The data collecting method includes observation, interview, test and document. Data collected in the form of (1) the observation results of teacher activity during the implementation of learning and respond and student learning outcomes; (2) student implementingthe learning process, the interview was also conducted to the students to obtain information of learning activity and outcomes. This study was conducted in 2 cycles; each cycle was consisting of 4 stages: planning, action, observation, and reflection. Learning by applying paired card game method makes students feel happy and motivated to learn math, so mathwas not a scary and boring subject anymore. Based on the observation of teachers,it can be seen that teacher activity in learning cycle 1 obtained a score of 78.4% (good), while the results of teacher activity observation on learning cycle 2 obtained a score of 93.8% (excellent). The final test results obtained in the study was also showed an increase in student learning outcomes, in cycle 1 there are 4 children who have not reached the KKM target, whereas in cycle 2 the result was satisfying that all 3rd graders have reached the KKM target.